INVESTIGATION ON LONG DISTANCE TRANSPORTATION OF FISH I. TRANSPORTATION OF FROZEN FISH FROM COCHIN TO CULCUTTA - GOVINDAN, T K; GUPTA, SIBSANKAR; CHATTOPADHYAY, P. CHATTOPADHYAY (Fishery Technology, 2017)
Oil Sardine ( Sardinella longfceps), mackerel ( Rastrelligerkanagurta), cat fish (Arius sp.), threadfin bream (Nemipterusjaponicus) and ribbon fish (Trichurus sp.) were frozen in glazed/unglazed blocks, packed in expanded polystyrene (EPS) insulatedplywood boxes with and without additional ice and despatchedin uninsulated parcel vans of trains from Cochin to Calcutta.The consignments reached the destination in excellent conditionand were readily disposed off.